Public opinion and features of media discourse in the Sociološki pregled / Sociological review - Jevtović, Zoran B; Vulić, Tatjana M (Sociološki pregled, 2018)
If we observe social activities as a dynamic, complex, individual, group and mass engagement towards meeting certain goals and ideas which subsequently affect the behavior of people, this paper shall emphasize an increasingly important role of sociology of mass communication, which creates and shapes public opinion through its examination of the process of identifcation, selection, shaping, storage and distribution of information. Starting from the notion of discourse and the understanding that human sciences believe that discourse leads to specifc activities that are concerned with a broader social environment and relationships, the authors of this paper use the method of content analysis of the texts published in the Sociološki pregled/ Sociological Review during eight decades in order to indicate that discourse can gain specifc power to symbolically inﬂuence and transform society only through mass media. Te results indicate that the frst glimpses of change when it comes to the view and opinion about politics were noticed in the frst text with a sociological and communicative approach (published in 1970), as it showed a slight professionalization of the creators of public opinion; moreover, the results have shown that the deep transformation began in the 1990s with a greater number of papers which dealt with public research, political propaganda, election campaigns, marketing, media systems, eﬀects and theories.Te fact that the number of such texts in the Sociološki pregled/ Sociological Review was increasing over time is also indicative of a change in the sociological paradigm and the democratization of the public, which nowadays cannot be pictured without media inﬂuence.